2005
DOI: 10.1111/j.1523-1755.2005.00416.x
|View full text |Cite
|
Sign up to set email alerts
|

A pilot randomized controlled trial of renal protection with pioglitazone in diabetic nephropathy

Abstract: In patients with advanced diabetic nephropathy, we found no reduction in proteinuria over 4 months. These data are useful to design larger studies with longer duration of follow-up to demonstrate renal protection of PPAR-gamma agonists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 45 publications
2
48
1
Order By: Relevance
“…Glipizide produced a mean increase in proteinuria of 6.1%, whereas pioglitazone therapy was followed by a proteinuria reduction of 7.2%. This difference, however, was not statistically significant (78).…”
Section: Diabetic Nephropathymentioning
confidence: 54%
See 1 more Smart Citation
“…Glipizide produced a mean increase in proteinuria of 6.1%, whereas pioglitazone therapy was followed by a proteinuria reduction of 7.2%. This difference, however, was not statistically significant (78).…”
Section: Diabetic Nephropathymentioning
confidence: 54%
“…At 12 months, UAE was also significantly lower in pioglitazone-treated patients in comparison with those treated with glibenclamide and voglibose (77). More recently, Agarwal et al (78) reported the result of a randomised, open-label, study comparing glipizide with pioglitazone over 16 weeks in 44 type 2 diabetic patients with overt diabetic nephropathy. Glipizide produced a mean increase in proteinuria of 6.1%, whereas pioglitazone therapy was followed by a proteinuria reduction of 7.2%.…”
Section: Diabetic Nephropathymentioning
confidence: 94%
“…146 Beyond their hypoglycemic actions, PPARЎ agonists exert a number of beneficial effects in diabetes including improvement in endothelial function, 147,148 reduction in pro-atherogenic inflammatory markers 149 and angiotensin-I and -II, 150 down regulation of AT 1 mRNA and protein in vascular smooth muscle cells, 151,152 decrease in urine endothelin-1 secretion, 153 attenuated lipid accumulation and its related injury in mesangial cells, 154,155 and inhibition of glomerular and tubular cell proliferation 156,157 . Several animal [158][159][160][161][162][163] and human studies 153,[164][165][166][167][168][169][170][171][172][173][174][175] using various TZDs have demonstrated a reduction in proteinuria and BP. Unfortunately; most of these studies were of short duration averaging 1-9 months in the animal studies 158-163 and 3-12 months in human studies.…”
Section: Emerging Therapeutic Agents For Diabetic Nephropathy Thiazolmentioning
confidence: 99%
“…Unfortunately; most of these studies were of short duration averaging 1-9 months in the animal studies 158-163 and 3-12 months in human studies. 153,[164][165][166][167][168][169][170][171][172][173][174][175] The use of TZDs has become less frequent due to higher rates of cardiovascular complications. A recent observational, retrospective, inception cohort of 227,571 Medicare patients who were treated with rosiglitazone or pioglitazone for a 12-month period and followed for up to 3 years after initiation of therapy showed rosiglitazone was associated with a higher risk of cardiovascular complications and all-cause mortality in patients 65 years or older compared with pioglitazone.…”
Section: Emerging Therapeutic Agents For Diabetic Nephropathy Thiazolmentioning
confidence: 99%
“…Pioglitazone shows protective effect on obesity related diabetic nephropathy by reducing renal oxidative damage and advance glycation end-product deposition 9 . In patients with advanced diabetic nephropathy pioglitazone reduces proteinuria over 4 months 10 . Nateglinide is a short-acting pancreatic beta-cellselective K(ATP) potassium channel blocker that binds rapidly to the sulfonylurea SUR1 receptor with a relatively low affinity and dissociates extreme rapidly with a unique "fast on-fast off" effect.…”
Section: Introductionmentioning
confidence: 99%